Microbiology of chronic suppurative otitis media: Experience at Dera Ismail Khan - Kamran Iqbal; Muhammad Ismail Khan; Luqman Satti (Gomal Journal of Medical Sciences, 2012)
Background: Chronic suppurative otitis media is a common infectious disease. The micro-organisms commonly associated with it and their antibiotic sensitivity pattern is important for its treatment. This study was conducted to identify the common microorganisms involved and their antibiotic sensitivity pattern in patients with chronic suppurative otitis media.